Pengaruh Budaya Organisasi Terhadap Produktivitas Kerja Guru di SMP Al-Farisi Tapos Bogor - Arizqi, Arizqi Ihsan Pratama; Asih Rahayu; Musthofa (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
The success and performance of teachers in the field of education is largely determined by organizational culture because it is seen as a factor that has an influence on increasing teacher work productivity. Many teachers do not pay attention to the organizational culture applied in schools which causes teacher work productivity to decrease so that it has an impact on the graduation (output) of students. The research method used is a quantitative approach. Data collection techniques using instruments or questionnaires. It is known that the results of statistical calculations using SPSS 22 show that there is a significant positive relationship between Organizational Culture (X) and Teacher Work Productivity (Y) at SMP Al-Farisi Tapos Bogor, as evidenced by Ryx = 0.470 which has a fairly deep relationship. range (0.400-0.600), the significant value and the value of the coefficient of determination are 24.6% and 74.4% are influenced by other factors. Such as education, skills, motivation, salary, health, technology, achievement opportunities and others.